FROM CLASSROOM TO COMMUNITY: BATIK-MAKING EDUCATION AS A MODEL OF CULTURAL PRESERVATION AND SOCIAL ENGAGEMENT FOR STUDENTS - Angga Fajar Ramadhan; Syakir Syakir; Djuli Djatiprambudi; Muhammad Ibnan Syarif (Universitas Labuhanbatu, 2026)
Purpose – Despite Indonesia’s Projek Penguatan Profil Pelajar Pancasila (P5), empirical evidence remains limited on how local-wisdom projects in secondary madrasahs operationalize equal school–community partnerships and through what mechanisms these partnerships shape students’ cultural identity and social engagement. This study examines a teacher–artisan co-teaching model and its outcomes for cultural identity and school–community engagement.Methodology – A qualitative case study was conducted at MA Ma'arif 20 Tarbiyatul Huda, Sendangduwur Village. The subjects were 73 students and 23 teachers. Data from participant observation, in-depth interviews, and documentation were analyzed thematically (reduction–appearance–conclusion) using CTL, collaborative learning, and cultural socialization as lenses. Triangulation and member checking supported data reliability.Findings – Thematic analysis revealed a six-phase project architecture culminating in a public exhibition, enabled by a distributed-expertise configuration: teachers coordinated learning objectives, reflection, and assessment; artisans taught core craft techniques and motif meanings; and alums mediated logistics and mentoring. Batik co-production fostered students' cultural identity pride, aesthetic literacy, and creative agency, while strengthening cooperation, responsibility, and empathy through task division, peer support, and public-facing accountability. The partnership also mitigated constraints such as limited specialist teacher capacity and the absence of formal batik teaching modules.Contribution – This study offers a replicable P5-oriented batik pedagogy model that formalizes artisans as co-educators and articulates design principles for curriculum support and sustainable school–community networks, particularly for madrasahs with constrained arts-teaching expertise and instructional infrastructure.